Current and future use of telemedicine in surgical clinics during and beyond COVID-19: A narrative review. (June 2021) - McMaster, Thomas; Wright, Timothy; Mori, Krinal; Stelmach, Wanda; To, Henry
Abstract: Introduction: Telemedicine has emerged as a powerful tool in the delivery of healthcare to surgical patients and enhances clinician-patient encounters during all phases of patient care. Our study aims were: to review the current use and applicability of telemedicine; evaluate its suitability, safety and effectiveness in a surgical outpatient setting, particularly in the era of social distancing restrictions and provide insight into future applications. Methods: Databases searched included: PubMed, OVID Medline, Embase, Scopus, Web of Science and review of reference lists. Key words used were "telemedicine"; "telehealth"; "videoconference"; "outpatient" and "surgical clinic". For inclusion, articles required to be in English, published between 2000 and 2021, were in an outpatient surgical setting and if they had a focus during the COVID-19 pandemic. Results: 335 articles were identified and screened, so that 63 articles were included in the review. Almost all articles were from Western countries (n = 60), mostly in surgical journals (n = 35) and from a range of sub-specialities, but pre-dominantly orthopaedics (n = 12) and general surgery (n = 7). The majority were original comparative studies where 31 studies directly compared telemedicine to in-person appointments and 14 papers focused on implementation during COVID-19. Discussion/conclusions: Telemedicine has been safely used across various phases of surgical outpatient care, with its effectiveness evaluated by clinical outcomes, economics and user/provider satisfaction. Telemedicine has multiple accepted benefits including time efficiency, patient/healthcare cost savings and community access, but with reported limitations of clinical uncertainty, technology infrastructure requirements, cybersecurity vulnerabilities and healthcare regulatory restraints. These limitations are being overcome by accelerated implementation during COVID-19 via fast-tracked practice development. Further work is required via development of research protocols to refine the application of emerging telemedicine technologies and their applicability to different surgical sub-specialties. Highlights: Telemedicine challenges the current model for delivery of surgical outpatient care. Telemedicine has been evaluated for use in pre-/post-operative surgical outpatient care. COVID-19 forced rapid protocol development for telemedicine use in surgical outpatient clinics. Telemedicine is safe & there are multiple models of how safety can be achieved. Future applications include enhanced communication, real-time monitoring & improved MDT care.